Registration of marriage and the protection conferred to Muslim married women in Malaysia - Md Hashim, Noraini (2012)
Introduction: In present daily life, proper registration of marriage is of extreme importance not only to the parties themselves but also to others (including government departments) who may wish to have evidence of their marriage. Registration as part of the legal formalities of marriage will ensure among others that the parties do not enter into marriage in an ill-considered or frivolous way, with the existence of a formal record of marriages, and that anyone who wishes to object to the marriage can do so. It begins with the Universal Declaration of Human Rights (herein after referred to as UDHR) in determining and ensuring equal rights for both spouses in connection with marriage, Convention on Consent to Marriage, Minimum Age for Marriage and Registration of Marriage (herein after referred to as the Convention) is established, in respond to Article 16 of the UDHR.